Clinical and morphological aspects of high-intensity focused ultrasound application in breast fibroadenoma treatment: 2-year post-operation survey results analysis - Suindyk Imankulov; Turlybek Tuganbekov; Kulsara Rustemova; Zhazira Seidagaliyeva; Nurlan Zhampeissov (National Scientific Medical Center, 2016)
Purpose of this study isto develop a new technique of HIFU treatment for breast fibroadenoma, analyze relation between ablation power and morphological results, verify effectiveness of the proposed method through comparison between the main (HIFU treatment) and the control (surgically treated) groups in terms of the immediate results, complications, and recurrences over two-year post-treatment period. Methods: The study involved 80 patients with breast fibroadenomas: 40 were HIFU-treated (main group) and others surgically (control). Conducted morphocytological study categorized fibroadenoma as intracanalicular, pericanalicular or mixed. We used Model-JC Focused Ultrasound Tumor Therapeutic System (Chongqing Haifu Medical Technology Co. Ltd., China) equipment with 1 MHz frequency, 21.5 cm lens diameter and 16.2 focused distance for HIFU treatment.For comparison analysis, results of morphological investigation and ultrasonography used for statistical analysis with software STATISTICA and IBMSPSS. We conducted in-vitro investigations and morphocytological study with 3 circular cross-sections of fibroadenomas ablated by HIFU with 100W, 200W, 300W. All patients were surveyed by Questionnaire SF-36 checking physical functioning, level of pain, overall well-being, etc. Results: No postoperative complications in main (HIFU) and 8 complications in control groups, 5 recurrences after 12-18 months were revealed in control group and 0 in main, inpatient stay duration was less by 52% in main group than in control group. Power ablation investigations show that 100W ablation created initial changes related to coagulation necrosis, full coagulation necrosis was observed at 200W and complete destruction of tissue at 300W. Questionnaire results shows that HIFU treatment reduced intensity of pain by 44.7% and stimulated early resumption of functional activeness by 66.7%. Conclusion: HIFU therapy is new effective treatment method for breast fibroadenoma, that has less post-treatment complications and recurrences than surgical method, and may be used as an independent treatment of breast fibroadenoma.